The New Geopolitical Reality and Its Impact on the Strategy for Economic and Social Development of Russia - Vladimir Alexandrovich Shamakhov; Aleksei Igorevich Balashov (Управленческое консультирование)
The article analyzes the causes of the transition of the Russian economy from 2013 to the prolonged stagnation has passed now in stagflation. The authors examine the effects of change emerged in the 2000s. Russia's growth model based on the conversion of oil and gas windfall in domestic demand, as well as a complex geopolitical factors, the state of uncertainty that adversely affects the economic and social development of modern Russia. In the result of the analysis the authors conclude that the real growth potential of the Russian Federation is now rooted in building the «weight» of Russia in the Eurasian geopolitical, economic and cultural space, the development of the Eurasian integration and the strengthening of the Shanghai Cooperation Organization through the instruments of «soft power» - science, education, intercultural exchanges, common professional and educational standards and training programs, especially in the field of public administration, corporate management and economics. The article substantiates the hypothesis that the strength of humanitarian cooperation, built around a unique polietichnoy Russian civilization is able to bring the present conditions of economic and social development of Russia on track for sustainable growth. At the end of the article the authors formulated a number of concrete proposals on the promotion of Eurasian integration in the field of formation of common professional and educational standards and training programs in the field of state and municipal government, some of which are already being implemented in the North-West Management Institute of the Russian President Academy of National Economy and Public Administration.